Electron-transfer-mediated decay and interatomic coulombic decay from the triply ionized states in argon dimers - Sakai, Kenji; Stoychev, S.; Ouchi, T.; Higuchi, I.; Schöffler, M.; Mazza, T.; Fukuzawa, H.; Nagaya, K.; Yao, M.; Tamenori, Y.; Kuleff, Alexander I.; Saito, N.; et al. (Physical review letters, 2011)
We report the first observation of electron-transfer-mediated decay (ETMD) and interatomic Coulombic decay (ICD) from the triply charged states with an inner-valence vacancy, using the Ar dimer as an example. These ETMD and ICD processes, which lead to fragmentation of Ar3+−Ar into Ar2+−Ar2+ and Ar3+−Ar+, respectively, are unambiguously identified by electron-ion-ion coincidence spectroscopy in which the kinetic energy of the ETMD or ICD electron and the kinetic energy release between the two fragment ions are measured in coincidence.
Gesehen am 30.09.2022